Glycosylation of CaV3.2 Channels Contributes to the Hyperalgesia in Peripheral Neuropathy of Type 1 Diabetes - Joksimovic, Sonja Lj.; Evans, J. Grayson; McIntire, William E.; Orestes, Peihan; Barrett, Paula Q.; Jevtovic-Todorovic, Vesna; Todorovic, Slobodan M. (Frontiers in Cellular Neuroscience, 2020)
Our previous studies implicated glycosylation of the CaV3.2 isoform of T-type Ca2+ channels (T-channels) in the development of Type 2 painful peripheral diabetic neuropathy (PDN). Here we investigated biophysical mechanisms underlying the modulation of recombinant CaV3.2 channel by de-glycosylation enzymes such as neuraminidase (NEU) and PNGase-F (PNG), as well as their behavioral and biochemical effects in painful PDN Type 1. In our in vitro study we used whole-cell recordings of current-voltage relationships to confirm that CaV3.2 current densities were decreased approximately 2-fold after de-glycosylation. Furthermore, de-glycosylation induced a significant depolarizing shift in the steady-state relationships for activation and inactivation while producing little effects on the kinetics of current deactivation and recovery from inactivation. PDN was induced in vivo by injections of streptozotocin (STZ) in adult female C57Bl/6j wild type (WT) mice, adult female Sprague Dawley rats and CaV3.2 knock-out (KO mice). Either NEU or vehicle (saline) were locally injected into the right hind paws or intrathecally. We found that injections of NEU, but not vehicle, completely reversed thermal and mechanical hyperalgesia in diabetic WT rats and mice. In contrast, NEU did not alter baseline thermal and mechanical sensitivity in the CaV3.2 KO mice which also failed to develop painful PDN. Finally, we used biochemical methods with gel-shift analysis to directly demonstrate that N-terminal fragments of native CaV3.2 channels in the dorsal root ganglia (DRG) are glycosylated in both healthy and diabetic animals. Our results demonstrate that in sensory neurons glycosylation-induced alterations in CaV3.2 channels in vivo directly enhance diabetic hyperalgesia, and that glycosylation inhibitors can be used to ameliorate painful symptoms in Type 1 diabetes. We expect that our studies may lead to a better understanding of the molecular mechanisms underlying painful PDN in an effort to facilitate the discovery of novel treatments for this intractable disease.